Analysis of Integrated Marketing Communication (IMC) Based Marketing Communication Strategies in Driving Generation Z's Purchase Intention for Eco-Friendly Sea Pandan Leaf Woven Products: A Case Study of Paraakar Indonesia - Dwi Salsabila, Alya; Novita Alim Putri, Rahma (representamen, 2026)
This study aims to analyze the application of Integrated Marketing Communication (IMC) strategies by Paraakar Indonesia in encouraging Generation Z's purchase intention towards eco-friendly sea pandan leaf woven products. The appropriate use of IMC on digital platforms, especially Instagram, is expected to increase the engagement of young audiences who are highly influenced by visual content and sustainability values. The method used is a descriptive case study by collecting data through observation of digital content from the @paraakar Instagram account and online documentation related to the brand. Data analysis techniques use content analysis and descriptive qualitative analysis to evaluate the quality of visual communication, message consistency, and interaction with the audience. The results of the study show that although Paraakar has integrated messages of sustainability and empowerment of local artisans, there are still shortcomings in terms of visual quality, interactivity, and consistency of the messages conveyed. This has resulted in low audience engagement and purchase intention among Generation Z. It is recommended that Paraakar strengthen its visual branding, increase the frequency of posts, and utilize interactive features to increase engagement and encourage purchasing decisions. Keywords: Sea pandan leaf weaving, Generation Z, Integrated Marketing Communication (IMC), Paraakar, Purchase intention.